Evaluation of Pharmacokinetic and Toxicological Parameters of Arnica Tincture after Dermal Application In Vivo (2022)
ABSTRACT: Cutaneous leishmaniasis (CL) is classified as a neglected tropical disease by the World Health Organization. As the standard drugs for the treatment of this disease suffer from severeunwanted effects, new effective and safe therapeutic options are required. In our previous work, Arnica tincture showed promising antileishmanial effects in vitro and in vivo. For the potential treatment of human CL patients with Arnica tincture, data on the pharmacokinetic properties of the bioactive, antileishmanial compounds (the sesquiterpene lactone (STL) helenalin and its derivatives) are needed. Therefore, we studied the in vivo absorption of the bioactive compounds after the dermal application of Arnica tincture in rats. Moreover, we analyzed the blood plasma, urine, and feces of the animals by ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry (UHPLC-HRMS). Although the majority (84%) of the applied STLs (1.0 mg) were absorbed, the concentrations in the plasma, urine, and feces were below the limit of detection (0.3 ng/mL) in the samples for UHPLC-HRMS analysis. This result may be explained by extensive metabolism and slow permeation accompanied by the accumulation of STLs in the skin, as described in our previous work. Accordingly, the plasma concentration of STLs after the topical application of Arnica tincture was very far from a dose where toxicity could be expected. Additionally, tests for corrosive or irritant activity as well as acute and repeated-dose dermal toxicity did not show any positive results after the administration of the amounts of Arnica tincture that would be needed for the treatment of CL. Consequently, in the treatment of CL patients with Arnica tincture, no toxic effects are expected, other than the known sensitization potential of the STLs.